Comparative studies on weldability and mechanical characteristics of semi- killed steel using different arc welding technique. (2022) - Muthukumaran, N.; Kathiresan, G; Shree Raam, M.N.; Chandru, G.; Dineshkumar, S.; Chiranjeevi, K.; Rajkumar, S.; Manikandan, M.; Arulmurugan, B.
Abstract: The main objective of this study is to examine the weldability and mechanical properties of semi-killed steel of E250BR grade which is mostly used in gear box casing. Three different arc welding methods i) GMAW (Gas Metal Arc Welding) ii) GTAW (Gas Tungsten Arc Welding), and iii) A-GTAW (Activated Gas Tungsten Arc Welding) were employed in this study, and the respective weld joints mechanical properties were evaluated and compared with each other. Visual inspection of the specimens shows that the GTAW and A-GTAW processes offer excellent weld bead geometry. Visual and radiographic inspections showed no crack or discontinuity is in the weld joints. The weldment produced by A-TIG welding has the highest aspect ratio, which is due to the reverse Marangoni convection effect. The tensile and hardness test outcomes exhibited that the mechanical properties of the parent metal were not affected by the welding processes, but impact test results showed a lack of energy absorption by the specimen from the A-GTAW process. A-GTAW welding had the highest Ultimate Tensile strength, which was 2.5 percent to 5 percent higher than the other processes employed in this study. Weldments fabricated using GTAW welding have the highest impact toughness, which is 43.5 percent and 51.85 percent more than the other two processes. Vickers hardness test reveals that joints made with the GTAW process are better than the other counter parts.